2012
DOI: 10.1002/ijc.27755
|View full text |Cite
|
Sign up to set email alerts
|

Local targets for immune therapy to cancer: Tumor draining lymph nodes and tumor microenvironment

Abstract: In recent years, it has become apparent that immunoregulatory processes influence cancer development. The key players in tumor progression are mainly present in the microenvironment of the tumor and the draining lymph nodes. Interventions aimed at shifting tumor-promoting actions toward effective tumor-eradicating immunity are thus foremost required locally. As immune-modulating therapy has been shown to cause many adverse side effects when administered systemically, we strongly advocate the further developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 70 publications
1
47
0
Order By: Relevance
“…Importantly, B cell lines did not undergo additional proliferation as a result of treatment with anti-CD20:CD40L. These findings are in agreement with earlier reports on therapeutic exploitation of CD40 and highlight our approach as a means of achieving loco-regional maturation of DC in the tumor micro-environment [13]. Furthermore, rational incorporation of scFv fragments into these fusion proteins can be used to confer additional anti-cancer effects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Importantly, B cell lines did not undergo additional proliferation as a result of treatment with anti-CD20:CD40L. These findings are in agreement with earlier reports on therapeutic exploitation of CD40 and highlight our approach as a means of achieving loco-regional maturation of DC in the tumor micro-environment [13]. Furthermore, rational incorporation of scFv fragments into these fusion proteins can be used to confer additional anti-cancer effects.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, dose-limiting toxicity using sCD40L or agonistic CD40 antibodies has been reported in humans [10-12]. Importantly, whereas systemic treatment with agonistic CD40 Abs in pre-clinical mouse models was associated with significant liver toxicity, local administration of agonistic CD40 Abs proved equally effective, yet without the associated toxicity [13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, TDLNs are directly influenced by tumor-derived immunosuppressive factors, which lead to decreased DC population and impaired DC maturation. Previous studies have shown that increasing mature DCs in TDLNs is crucial for eliciting effective anti- tumor immune responses and tumor eradication [33]. We therefore investigated the effect of different vaccines on DC population in TDLNs.…”
Section: Immunization Of Pmp/ova/sirna Increased Mature DC But Decreamentioning
confidence: 99%
“…23 As antitumor T cell priming occurs in tumor draining lymph nodes, 24 we first examined IFN-g-expressing T cells in tumor draining lymph nodes. Compared to the animals receiving the blank hydrogel treatment, the treatments using the hydrogels carrying either celecoxib or anti-PD-1 mAb did not significantly increase the percentage of IFN-g-expressing CD4…”
Section: Dual Delivery Of Celecoxib and Anti-pd-1 Mab Elicits A Synermentioning
confidence: 99%